2017
DOI: 10.17507/jltr.0805.14
|View full text |Cite
|
Sign up to set email alerts
|

The Realization of Intensifiers in Banyumas Dialect

Abstract: Abstract-Linguistic provides a set of devices to express referential and affective functions. Intensifier as a linguistic device is generally found in all languages and it has various linguistic forms. In Banyumas dialect, a substandard of Javanese language, intensifier is basically used to intensify something. Banyumas dialect or Banyumasan is primarily spoken along Serayu River. Banyumas dialect is different from Javanese language in respect of phonological features and lexical items. Speakers express their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Using Rule 1, interlinear glosses were aligned vertically, word by word, with the example. Next, intensifiers were categorised into lexical items (with general and specific functions) and reduplication based on Hadiati (2017). Finally, the intensifiers were categorised based on their intensity into maximizer and booster.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using Rule 1, interlinear glosses were aligned vertically, word by word, with the example. Next, intensifiers were categorised into lexical items (with general and specific functions) and reduplication based on Hadiati (2017). Finally, the intensifiers were categorised based on their intensity into maximizer and booster.…”
Section: Methodsmentioning
confidence: 99%
“…Intensifiers in Siquijodnon (spoken in the Philippines) which carry the meaning of "so" and "very" are kayo, baling, perte/perting and grabi/grabing and can be used with any adjective (Bantawig & Marano, 2017). Hadiati (2017) found that intensifiers in the Banyumas dialect in Indonesia are realised into lexical items and reduplication, based on an analysis of natural conversations using the Leipzig Glossing Rule (Bickel et al, 2015). Her results also showed that lexical items can be further classified into general intensifiers (free intensifiers which are found after adjectives and rarely in front of adjectives) and specific intensifiers restricted to certain adjectives.…”
Section: Adjectives and Intensifiers In Austronesian Languagesmentioning
confidence: 99%
See 3 more Smart Citations